Analisis Kesehatan Lingkungan Rumah, Penyuluhan dan Pelatihan Pencegahan Tuberkulosis (TB) di Bantul, Yogyakarta - Surahma Asti Mulasari (Universitas Mathla'ul Anwar Banten, 2019)
HOME ENVIRONMENTAL HEALTH ANALYSIS, COUNSELING AND TUBERCULOSIS PREVENTION TRAINING (TB) IN BANTUL, YOGYAKARTA. Tuberculosis (TB) is an infectious disease caused by the bacterium Mycobacterium tuberculosis, this disease can attack various organs, especially the lungs. This disease, if left untreated or incomplete treatment, can cause dangerous complications to death, and potential to spread to other people. In Hamlet